IMPROVEMENT AND STRENGTHENING OF INTEGRATED LESSONS IN ELEMENTERY SCHOOL CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the process of teaching natural science, the foundations of a scientific worldview are formed in school children (the teacher consistently reveals the materiality and interrelationship of natural objects and events, characterizes the constant changes that occur in nature, etc.), aesthetic feelings, love for nature, care for it and the desire to protect it are brought up. A science teacher should choose the methods of teaching in such a way that, as a result, geographical knowledge and skills are formed in the student's mind.